Sekolah Balita sebagai Upaya Pendampingan Pengentasan Gizi Buruk pada Balita di Kelurahan Bulak Banteng Surabaya - Muchlashin, Anif; Ansori, Teguh (LP2M INSURI Ponorogo, 2020)
The purpose of this study is to improve the nutritional status of toddlers whose status is still at the threshold below the red line (BGM - Bawah Garis Merah) and malnutrition that mostly caused by parenting practices that do not meet health standards. Child feeding, food menu presentation, and environmental hygiene were among several factors that cause the occurrence of BGM and malnutrition in toddlers in Bulak Banteng village of Kenjeran District, Surabaya City. In this program, the researchers used the Participatory Action Research (PAR) social research method that consists of three interconnected words (participation, research and action). In the process, researchers come with nutritionists, Posyandu cadres, and toddlers’ mothers who are affected by malnutrition. The first program creates study groups to make it easier to organize and research together, called Toddler School